PERANCANGAN SISTEM PENGAMBILAN KEPUTUSAN DALAM MENENTUKAN KUALITAS PRODUK DETERJEN BU KRIM MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS (STUDY KASUS: PT. MANDIRI INVESTAMA SEJATI ) - Muslim Alamsyah (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Yudharta Pasuruan)
Investama PT Mandiri Sejati is a company engaged in the industry is one of them producing detergent. There are so many factors to be considered in determining the quality of production to be produced per day which will be targeted in starting a business. The problem faced is determining product quality detergent which is still manual calculations. Has developed a new system that is implemented in a decision support system. This system is used to help facilitate the processing of data in determining the quality of the detergent. The entire data collection related in determining the quality of the data detergents include color, texture, scent and cleaning power. The method used for data processing using AHP (Analytic Hierarchy Process). Stages in AHP begins the process of defining the problem, the manufacture of structural hierarchy that begins with a general purpose, followed by the criteria and alternatives options, Test consistency hierarchy. If it does not comply with CR <0.100 then the assessment should be repeated again. The results showed that application of decision support systems are used to determine the quality of this detergen, it can perform calculations with AHP (Analytic Hierarchy Process) is faster than manual calculation so that it can be more efficient and the accuracy of the data is close to perfect.